Vibratome Sectioning and Clearing for Easing Studies of Cassava Embryo Formation - Lentini, Zaida; Tabares, Eddie; Buitrago, María E. (Frontiers in Plant Science, 2020)
This work describes the application of clearing on vibratome sections to study the embryo formation in cassava. This procedure provides high-resolution images and reduces significantly the number of sections that need to be analyzed per ovule. This methodology was instrumental for the development of the protocol for embryo rescue in cassava. It has been also applied to monitor the embryo formation response when optimizing seed setting from regular and broad crosses for cassava breeding. Broad crosses between cassava and castor bean (incompatible-euphorbiaceae species) were made aiming to induce doubled haploids through the elimination of the incompatible-male parent genome as done in cereals. Castor bean is widely available and provides continues supply of pollen. Our results suggest that this methodology is easy and effective to assess the response of hundreds of cassava ovules pollinated with castor bean pollen, allowing the identification of multicellular structures in the embryo sac without apparent formation of endosperm. The protocol is also useful when developing and optimizing a methodology to induce doubled haploids in cassava via gynogenesis or from ovules pollinated with irradiated cassava pollen.